Investigation of N behavior during coal pyrolysis and oxidation using ReaxFF molecular dynamics. (1st December 2018) - Zheng, Mo; Li, Xiaoxia; Guo, Li
Highlights: Nitrogen behaviors during coal pyrolysis and oxidation was explored by ReaxFF MD. A fuel lean oxidation system was constructed with a large-scale coal model. More than 65% N still remains in C40+ fragments after pyrolysis stage. Evolving trends, structures and reactions of light species with N were obtained. Hydrogen abstraction of N–H in N-5 by O2 is the first reaction for oxidation. Abstract: This paper presents ReaxFF molecular dynamics simulations of pyrolysis and oxidation processes at 500–2500 K and 1000–2800 K performed using the GPU-enabled ReaxFF MD code of GMD-Reax and reaction analysis code of VARxMD. The simulation results of a large-scale coal model with varied types of N-containing groups shows that more than 65% N still remains in C40+ fragments and about 25% N migrates into C5 –C40 fragments after pyrolysis stage. The evolution tendencies of light gases (NH3, HCN, HNCO, NO, N2 and NO2 ) and important radicals (CN, NH2 /NH, NCO and HNO) with temperature were observed from the slow heat-up coal oxidation simulation at fuel lean condition. The detailed structures and conversion reactions associated with light nitrogen species were obtained. The NCO-containing intermediates are found playing a significant role for NO emission that more than 50% of the NO formation is through NCO-containing intermediates, some of which comes from the oxidation of CN radicals and HNCO. The hydrogen abstraction of N–H in pyrrole groups by O2 will create an initial unstable environment, followed with O insertion reactions into N-containing heterocyclic ring structures to promote the activation of N-containing groups in coal structure.